Secondary school students’ views on digital education in relation to online opportunities in higher education - Bernhardt Renáta (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. According to Unicef, approximately 91% of the world’s enrolled students were affected when schools across continents closed down to help decrease the spread of COVID-19 (Unicef, 20191). Governments and professionals of the education system have been engaged in determining ways to implement digital and remote learning methods to ensure children continue to get their education even if they are confined to their homes. Although the lack of access to electricity, devices, resources and the internet could be realized, directors and teachers of schools have taken measures to address these disparities with innovative answers. In Hungary due to technology, remote learning, and teaching from home were not impossible, but it was a shocking period in March 2019. The efficiency of the educational process in digital work schedules has been examined from several perspectives in recent years (Furcsa 2019; Malatyinszky 2020, N. Kollár 2021). Furcsa and Szaszkó (2022) explored various components related to digital remote education and emphasized the significance of online education related ethical considerations as well as students’ anxiety, digital competences, self-efficacy as well as the role of teachers’s self-development and selfassessment related to their digital competences (Szaszkó 2019). Furthermore results show that there is a great diversity in the structural design of online distance education and the consistent application of the systems developed (Kisné Bernhardt, Furcsa, Sinka & Szaszkó 2021). The exploration of secondary school students' experiences with digital education also aims to formulate recommendations for online higher education courses in terms of outcomes. The opinion of 15-19 year old students (potential university students) is relevant because the form of online teaching and the methodology of online monitoring and evaluation are becoming more and more widespread in the higher education system.
Metaforakutatás a középiskolás diákok digitális oktatásról alkotott nézeteiről, tekintettel a felsőoktatás online lehetőségeire
Keywords: metaphor; digital education; secondary school students; higher education